Predation of Archilestris capnoptera (Wiedemann, 1828) (Diptera, Asilidae) by a Salticidae spider in campo rupestre associated with the Atlantic Forest, Brazil (Somma: Revista Científica do Instituto Federal do Piauí, 2026)
The family Asilidae (Diptera) comprises active predators with a wide distribution across Brazilian terrestrial ecosystems. Despite their predatory behavior, asilids may also serve as prey, although documented records of such interactions remain scarce. In this study, we report for the first time the predation of Archilestris capnoptera (Wiedemann, 1828) by a spider of the family Salticidae in a “campo rupestre” area associated with the Atlantic Forest biome. The event took place under conditions that suggest temporal and spatial overlap between the two predators, characterizing a case of intraguild predation. This record expands the knowledge on underreported trophic interactions among predatory arthropods and reinforces the importance of protected areas for the maintenance of complex ecological processes in highly biodiverse and threatened environments such as the “campo rupestre”.